Altogether lovely : a thematic and intertextual reading of the Song of Songs - Dharamraj, Havilah (Minneapolis. Fortress Press., 2018)
In Altogether Lovely, Havilah Dharamraj approaches the Song with a clear vision of the gendering of power relationships in the ancient Near East and through an intertextual method centered not on production but on the reception of texts. She sets the Song's lyrical portrayal of passion and intimacy alongside other canonical portrayals of love spurned, lust, rejection, and sexual violence from Hosea, Ezekiel, and Isaiah. The result is a richly nuanced exposition of the possibilities of intimacy and remorse in interhuman and divine-human relationship.
Introduction -- Part I. Love in Separation. The Streets and Squares; The Wilderness -- Part II. In Praise of the Beloved. The Golden One; The Foundling -- Part III. Gardens. The Orchard of Pomegranates; The Vineyard -- Part IV. Love-and-Its-Jealousy. The Unquenchable Love; Insatiable Lust -- Conclusion.
Includes bibliographical references (pages 259-278) and indexes.
Keywords: Bible. -- Song of Solomon -- Criticism, interpretation, etc; Bible. -- Song of Solomon; RELIGION -- Biblical Studies -- Exegesis & Hermeneutics